Pengaruh Konflik Muhammadiyah Dan Haji Misbach Terhadap Pergerakan Muhammadiyah di Surakarta (1922-1926) - Setyorini, Fitri Sari; Khalid, Wahid Ibnu (Tasamuh: Jurnal Studi Islam, 2022)
This paper discusses the history of Haji Misbach's conflict with Muhammadiyah and its influence on the Muhammadiyah movement in Surakarta. This research uses the historical method with literature review. The sources used are archives, books, journals, newspapers. Historical and sociological approaches and conflict theory are used as analytical blades on the topic of discussion. The conflict between Haji Misbach and Muhammadiyah shows that: First, the conflict that occurs is due to differences of opinion related to the terminology of true Islamic attitudes. Second, the impact of the conflict on the Muhammadiyah movement in Surakarta from 1922 to 1926 was that Muhammadiyah Surakarta became the first organization to reject communism because it was considered to be damaging to Islamic unity. To strengthen this, Muhammadiyah Surakarta made several agendas of struggle that could suppress the development of communism. Muhammadiyah Surakarta established communist ideology both nationally and communist Islam as the enemy of the Muhammadiyah modernist movement. Muhammadiyah rejected political movements that could threaten the development of Islamic unity in the Dutch East Indies.